2015
DOI: 10.1161/atvbaha.115.306035
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Free DNA Modulates Clot Structure and Impairs Fibrinolysis in Sepsis

Abstract: Objectives-Sepsis is characterized by systemic activation of inflammation and coagulation in response to infection. In sepsis, activated neutrophils extrude neutrophil extracellular traps composed of cell-free DNA (CFDNA) that not only trap pathogens but also provide a stimulus for clot formation. Although the effect of CFDNA on coagulation has been extensively studied, much less is known about the impact of CFDNA on fibrinolysis. To address this, we (1) investigated the relationship between CFDNA levels and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
150
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(158 citation statements)
references
References 60 publications
2
150
0
6
Order By: Relevance
“…However, it remains to be identified what drives the hypecoaguability and fibrinolysis shutdown after trauma. Recent work in sepsis indicated that cell free DNA contributes to fibrinolysis resistance(27). These DNA fragments, which co-localize to histones, have been proposed to be drivers of microvascular thrombosis in septic shock(28).…”
Section: Discussionmentioning
confidence: 99%
“…However, it remains to be identified what drives the hypecoaguability and fibrinolysis shutdown after trauma. Recent work in sepsis indicated that cell free DNA contributes to fibrinolysis resistance(27). These DNA fragments, which co-localize to histones, have been proposed to be drivers of microvascular thrombosis in septic shock(28).…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22] Increased NET formation and accumulation may occur before, or close to the disease onset without proper clearance mechanisms, as shown for traumatized or septic adults. 39,40 NET formation in the intestine with released DNA and neutrophil-derived calprotectin has been shown to be associated with NEC, 26 but it was not clear if circulating NETs may play a role. In the present study, elevated circulating cfDNA levels 1-6 d before NEC onset in preterm infants suggest that sub-clinical systemic inflammation at an early stage of NEC may stimulate neutrophils to release DNA and antimicrobial proteins in the circulation, which may add further inflammatory insults that could advance NEC progression.…”
Section: Discussionmentioning
confidence: 99%
“…147 NETosis may also influence fibrinolysis and thrombus stability, as the addition of CF-DNA and histones to clotting plasma results in the formation of thicker fibers with greater mechanical stability. 148 In patients with sepsis and elevated CF-DNA levels, clot lysis times are attenuated compared with controls 149 ; this effect can be replicated by the addition of histone-DNA complex 148 or in the presence of NETing neutrophils. 53 The presence of CF-DNA within the clot has been shown to impair plasminogen activation by tPA, 53 and the binding of plasmin to fibrin.…”
Section: Fibrinolysismentioning
confidence: 98%